2018
DOI: 10.1007/s00268-018-4488-y
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery (MIS) in Children and Adolescents with Pheochromocytomas and Retroperitoneal Paragangliomas: Experiences in 42 Patients

Abstract: PH and PGL in children and adolescents should preferably be removed by minimally invasive surgery. Partial adrenalectomy provides long-term steroid independence in bilateral PH and a low rate of (ipsilateral) recurrence. α-Receptor blockade may not be necessary in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Of note, endoscopic surgery is now also standard for extra-adrenal retroperitoneal pheochromocytoma and even a good option for pelvic and thoracic pheochromocytoma (Fig. 2) (Walz et al 2006(Walz et al , 2018.…”
Section: Answer 3: Treatment Optionsmentioning
confidence: 99%
“…Of note, endoscopic surgery is now also standard for extra-adrenal retroperitoneal pheochromocytoma and even a good option for pelvic and thoracic pheochromocytoma (Fig. 2) (Walz et al 2006(Walz et al , 2018.…”
Section: Answer 3: Treatment Optionsmentioning
confidence: 99%
“…The study by Amar et al (36) regarding the factors affecting the recurrences in pheochromocytoma shows that recurrence is impacted by the dimensions of the tumor, affected location (right side is more likely than the left side) and diagnosis age (recurrence is much more observed amongst the youth). Walz et al (37), in their study dated back to 2018 in which an assessment was made for the minimal invasive TA and PA for 70 adrenal masses observed on the patients involving 42 children and adolescents with pheochromocytoma and/or paraganlioma, (26 with pheochromocytoma, 11 PGL and 5 pheochromocytoma + PGL) reported that 31 of the patients with pheochromocytoma underwent PA while excision was made for the patients with PGL. During the follow up period of 8.5 years as an average, recurrence was observed in two patients with VHL syndrome in the case of PA and out of five PGL patients with recurrence, four patients had to undergo another operation.…”
Section: Oncologic Resultsmentioning
confidence: 99%
“…26,27 A mini-invasive approach is feasible but it should be performed preferably in tertiary centers with high volumes of oncologic cases and laparoscopic procedures in the pediatric population. 24,25,28 This is justified in order to minimize the possible onset of severe intraoperative complications (such as severe bleeding) and to maximize the benefit of laparoscopic surgery. Moreover, the possible need of intensive postoperative monitoring should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%